Kebebasan Beragama Dalam Pendidikan (Studi di SMA Negeri 1 Blangpidie Aceh Barat Daya) - Masra Masra (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2016)
The author examines religious freedom in education in school SMA Negeri I Blangpidie, this is very interesting because freedom of religion is Human Rights. This work analyzes the freedom of religion in education. There are issues that must be considered by the teacher in the face of Muslim students and non-Muslim students. A teacher must not distinguish between the two groups. The data collected in this study through the data Descriptive, the authors also use the method of literature review and field methods. Researchers also interviewed the principal and two other teachers and students as many as 20 people and made some observations at the school. As for the purpose of research in this work was to determine whether the religious freedom be realized or not realized in SMA I Blangpidie. Based on the analysis that has been done it can be seen that the freedom of religion in education became one of the things that are new to the world of education. Where freedom of religion into human rights and religious freedom became universal and the prevailing belief is reflected in the International Human Rights instruments. In education of religious freedom became a new lesson in which the students have to understand that that in religion taught us to respect the religion one religion to another, and should not blame each other what to do by their respective religions, because it is her religious beliefs. And can provide the positive side for the students where Muslim students can socialize with non-Muslim students and Muslim students with non-Muslim students could transfer knowledge fellows. Negative side that should be considered not to students misunderstand the meaning of religious freedom. If this happens then the students easily converted and broken promises to their respective religions. Therefore, students will make themselves easily and as he converted.